HEAT TRANSFER FROM A SLIGHTLY CURVED CONVEX SURFACE - Can, Omer F.; Ozgen, Filiz; Celik, Nevin; Dagtekin, Ihsan (Begell House Inc, 2023)
This study is prepared to analyze the heat transfer from a uniformly heated, slightly curved convex (SCX) surface numerically using computational fluid dynamics (CFD) code of commercial software ANSYS-CFX. Some experimental results are also obtained by means of a wind tunnel setup to confirm the results of numerical study. After a good agreement is achieved between the experimental and numerical results, the effects of some major parameters on heat transfer around the SCX surface are determined by using numerical results. Effects of Prandtl number (Pr = 0.237 to 3431), Reynolds number (Re = 40,000 and 400,000), and curvature ratio (CR = 1, 2, and 4) on local Nusselt number (Nu) along the circumference of SCX are the extracted results. Additionally, new correlations of Nu depending on Re, Pr, and CR are obtained.The prime outcomes of this mathematical investigation are provided here. An exact numerical CFD solution is provided for the turbulent external flow around the curved surface appearing in this study. The graphical solutions of Nu number that show the heat transfer rate of the system can be divided into three regions for various Re numbers. The maximum average heat transfer is observed in the case of higher curvature ratio.
Keywords: curved-convex surface; external flow; Prandtl numbers; CFD